2019
DOI: 10.1177/0170840619835245
|View full text |Cite
|
Sign up to set email alerts
|

Legal infrastructures: How laws matter in the organization of new markets

Abstract: Research into the creation of markets highlights the importance of law-making, seen to express relations between stakeholders in emerging organizational fields. Less understood is the role of existing regulation, despite related work on path-dependency. We unpack the role of extant laws by analysing consecutive attempts to establish the mortgage market in post-socialist Hungary, mobilizing the anthropology of law and actor-network methods. Based on interviews and archival documents, we find, first, that existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…By paying attention to policy tools and legislation, our study has shown mundane processes that reshape the conditions for digitalization in a current public-sector context. In this way, the article makes an empirical contribution to the burgeoning literature, which focuses on the importance of law in organizations (Pellandini-Simányi and Vargha 2021). Second, using the double darkness as an analytical lens on digital-ready legislation leads us to rethink the problem of digitalization differently than other contributions on the dark sides of digitalization (e.g., Zuboff 2019; O’Neil 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By paying attention to policy tools and legislation, our study has shown mundane processes that reshape the conditions for digitalization in a current public-sector context. In this way, the article makes an empirical contribution to the burgeoning literature, which focuses on the importance of law in organizations (Pellandini-Simányi and Vargha 2021). Second, using the double darkness as an analytical lens on digital-ready legislation leads us to rethink the problem of digitalization differently than other contributions on the dark sides of digitalization (e.g., Zuboff 2019; O’Neil 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, as pointed out by scholars who have studied seemingly mundane, highly technical, and presumably boring details of, for example, auditing (Power 1999), administrative law (Latour 2010), or waste management (Woolgar and Neyland 2013), such practices are powerful partly because they are perceived as merely technical and boring. They are powerful because they are elements in infrastructures that shape organizations in ways that have a significant influence on key organizational actors and mechanisms (Pellandini-Simányi and Vargha 2021). Often, unobtrusive and seemingly neutral policy tools play a major role in these shaping processes (Lascoumes and Le Gales 2007).…”
Section: Introductionmentioning
confidence: 99%